Assessing the GRIP of Ventral Hernia Repair: How to Securely Fasten DIS Classified Meshes - Kallinowski, Friedrich; Harder, F.; Gutjahr, D.; Raschidi, R.; Silva, T. G.; Vollmer, M.; Nessel, Regine (Frontiers in Surgery, 2018)
Recurrences are frequently observed after ventral hernia repair. Based on clinical data, the mesh-defect area ratio (MDAR) can lead to lower recurrence rates. Using dynamic impact strain in a pig tissue model, MDAR can be modified to give a measure called grip to better assess the mechanical stability of ventral hernia repair. The focus of this experimental study is to assess the different aspects of mesh overlap and fixation only in bridging repair of ventral hernias. Dynamic impact strain (DIS) mimics coughing actions in an ex-vivo-model with the repetition of submaximal impacts delivered via a hydraulically driven plastic containment. Tissue derived from pig bellies simulates a ventral hernia with varying defect sizes. MDAR is calculated from the hernia orifice and the mesh overlap. Commercially available meshes were strengthened with glue, tacks and sutures to bridge the defects. The reconstructions are strained with up to 425 dynamic impacts. The grip of each repair is assessed using MDAR modified by the strength of the fixation. The DIS classification is based upon bridging of a 5 cm ventral hernia orifice with an overlap of 5 cm in a sublay position. The classification discriminates meshes properties upon DIS strain. MDAR is calculated to be 9 under these conditions. Decreasing the overlap or increasing the hernia orifice reduces MDAR to numbers below 9. MDAR is modified to reach GRIP. Plotting the likelihood of a bridging repair to survive more than 400 DIS impacts versus the grip estimated from the factors given above, the grip to be passed for a durable repair is 10 for Parietex Progrip® and Dynamesh Cicat® and 25 for Dynamesh IPOM®. Clinical data previously published can be reculculated to assess MDAR and permit an estimation of the grip of the reconstruction. In these recalculations, a correlation between MDAR and long-term recurrence rates is found. A dimensionless number called grip can be calculated. The grip can be modified by fixation in a reproducible way. A higher grip can improve the durability of ventral hernia repair. We believe that a higher grip leads to lower recurrence rates in the clinical setting. The DIS classification